Traumatic globe avulsion secondary to a penetrating orbital injury from a bicycle handlebar: a case report - Nishanth S. Iyengar; Edward Xie; Patricia Pahk; Nariman S. Boyle (Journal of Trauma and Injury, 2025)
A 60-year-old man presented with total avulsion of the right globe following a penetrating injury to the right orbit from a metal bicycle handlebar. There was no light perception in the right eye on presentation. External examination revealed a full-thickness, canalicular-involving, horizontal right upper eyelid laceration through which the luxated globe and other orbital contents extruded. The globe was intact. The patient underwent urgent surgical exploration. In the operating room the optic nerve and all extraocular muscles were found to be completely transected from the globe. The globe was enucleated, and the eyelid laceration was repaired with bicanalicular stent placement.